The association between changes in pressure pain sensitivity and changes in cardiovascular physiological factors associated with persistent stress. (March 2014) - Ballegaard, Søren; Petersen, Pernille B.; Harboe, Gitte S.; Karpatschof, Benny; Gyntelberg, Finn; Faber, Jens
Abstract Objectives. To evaluate the possible association between pressure pain sensitivity of the chest bone (PPS) and cardiovascular physiological factors related to persistent stress in connection with a three-month PPS-guided stress-reducing experimental intervention programme. Methods. Forty-two office workers with an elevated PPS (≥ 60 arbitrary units) as a sign of increased level of persistent stress, completed a single-blinded cluster randomized controlled trial. The active treatment was a PPS (self-measurement)-guided stress management programme. Primary endpoints: Blood pressure (BP), heart rate (HR) and work of the heart measured as Pressure-Rate-Product (PRP); Secondary endpoints: Other features of the metabolic syndrome. Results. PPS decreased and changes in PPS after the intervention period were significantly associated with HR, PRP, body mass index (BMI) and visceral fat index (all correlation coefficients > 0.2, p < 0.05). Compared to the control cluster group, the active cluster group obtained a significant reduction in PPS, Low-density lipoprotein (LDL) cholesterol and total number of elevated risk factors (p < 0.05). On an individual level, significant and clinically relevant between-group reductions were observed in respect to BP, HR, PRP, total and LDL cholesterol, and total number of elevated risk factors (p < 0.05). Conclusions. The stress intervention method applied in this study induced a decrease in PPS which was associated with a clinically relevant decrease in resting blood pressure, heart rate, work of the heart and serum cholesterols.